11 PMCA1 and arrhythmias: does deletion of PMCA1 lead to heart rhythm instability?. (17th November 2015) - Wilson, C; Zi, M; Cartwright, EJ
Abstract : Arrhythmic events are a common consequence of cardiomyopathies, continuing to be a leading cause of death and disability. By identifying mechanisms which increase arrhythmia susceptibility, therapeutic advancements can be made. Genetics are known to influence arrhythmia development during heart failure and one gene linked to several features of heart failure is the plasma membrane calcium ATPase 1 (PMCA1). Therefore, along with its role in hypertension, we believe PMCA1 may also influence heart rhythm stability and consequently the development of arrhythmias. To determine the role of PMCA1 in cardiac electrical activity, electrocardiograms (ECG) were performed on cardiomyocyte-specific knockout mice (PMCA1CKO) and mice heterozygous for PMCA1 (PMCA1Ht). Complete cardiomyocyte deletion of PMCA1 resulted in abnormal heart rhythms related to cardiac repolarisation dysfunction, prolonged QT and JT intervals (p = < 0.01), as well as increased susceptibility to arrhythmic events following programmed electrical stimulation. However, heterozygous PMCA1 expression had no significant effect on electrophysiological properties or arrhythmia susceptibility. With PMCA1CKO mice exhibiting abnormal heart rhythms, we began to characterise ion channel remodelling using RT-qPCR. Multiple cardiac ion channels were shown to have altered mRNA expression in PMCA1CKO mice. Notably, due to their involvement in cardiac repolarisation and arrhythmia development, genes encoding Nav1.5 (p = < 0.05), the L-type Ca 2+ channel (p = < 0.01) and Kv4.2 (p = < 0.05) were downregulated following cardiomyocyte-specific deletion of PMCA1. In conclusion, PMCA1 influences cardiac electrical activity and appears to effect arrhythmia susceptibility through ion channel remodelling. It is therefore becoming increasingly apparent that PMCA1 influences several of the central features of heart failure including heart rhythm abnormalities.